Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3346/jkms.2018.33.e27
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcopenia in Patients with Hip Fracture Is Related with High Mortality

Abstract: BackgroundThis study evaluated the prevalence of osteosarcopenia, as well as the relationship between one-year mortality and osteosarcopenia, as defined by criteria of the Asian Working Group on Sarcopenia in patients age 60 or older with hip fracture.MethodsA total of 324 patients age 60 years or older with hip fracture were enrolled in this retrospective observational study. The main outcome measure was the prevalence of osteosarcopenia, as well as the relationship between osteosarcopenia and 1-year mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 22 publications
(22 reference statements)
2
96
0
2
Order By: Relevance
“…is difference may be due to the fact that their cohort included only men, while in this study, the majority was women, who have shown to have a higher prevalence of muscle mass loss [9]. Another study showed a prevalence of osteosarcopenia of 27% and sarcopenia of 10% [4]. Something more similar to our study was seen in the study by Yoo et al [21] where the reported prevalence of sarcopenia was 44% in women and 68% in men who had had a previous fracture.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…is difference may be due to the fact that their cohort included only men, while in this study, the majority was women, who have shown to have a higher prevalence of muscle mass loss [9]. Another study showed a prevalence of osteosarcopenia of 27% and sarcopenia of 10% [4]. Something more similar to our study was seen in the study by Yoo et al [21] where the reported prevalence of sarcopenia was 44% in women and 68% in men who had had a previous fracture.…”
Section: Discussionmentioning
confidence: 57%
“…e term osteosarcopenia was recently proposed to describe the coexistence of both conditions in the same patient [3]. It has been shown that this combination represents an even greater risk of these results than any of the conditions alone [4].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of osteosarcopenia in community‐dwelling older adults ranges from 4.7% in Japan, to 13% in China and 28% in Germany, with the highest rates observed in Australia (40%) and Iran (34%) (N. Fahimfar, unpublished data, June 2019). A study of older Koreans with hip fractures also found that 27.2% were osteosarcopenic . The varied prevalence is likely due to heterogenous populations or a non‐unified diagnostic criterion for this syndrome, with various screening tools being utilized for low muscle mass and function (sarcopenia), a key component of osteosarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…A study of Chinese adults (≥65 years old) identified osteosarcopenia in 10.4% of men and 15.1% of women, with higher odds of frailty in the osteosarcopenics, relative to osteopororic or sarcopenic patients alone (55). In patients with hip fractures and osteosarcopenia, the 1-year mortality rate was 15.1%, compared to 5.1% for osteoporotic or 10.3% for sarcopenic patients (56). Future therapies could embrace both osteoporosis and sarcopenia by targeting pathways that affect both muscle and bone.…”
Section: Osteosarcopeniamentioning
confidence: 99%